Distinct Roles of the Repeat-Containing Regions and Effector Domains of the Vibrio vulnificus Multifunctional-Autoprocessing Repeats-in-Toxin (MARTX) Toxin - Kim, Byoung Sik (mBio, 2015)
Vibrio vulnificus is a seafood-borne pathogen that destroys the intestinal epithelium, leading to rapid bacterial dissemination and death. The most important virulence factor is the multifunctional-autoprocessing repeats-in-toxin (MARTX) toxin comprised of effector domains in the center region flanked by long repeat-containing regions which are well conserved among MARTX toxins and predicted to translocate effector domains. Here, we examined the role of the repeat-containing regions using a modified V. vulnificus MARTX (MARTX(Vv)) toxin generated by replacing all the internal effector domains with β-lactamase (Bla). Bla activity was detected in secretions from the bacterium and also in the cytosol of intoxicated epithelial cells. The modified MARTX(Vv) toxin without effector domains retained its necrotic activity but lost its cell-rounding activity. Further, deletion of the carboxyl-terminal repeat-containing region blocked toxin secretion from the bacterium. Deletion of the amino-terminal repeat-containing region had no effect on secretion but completely abolished translocation and necrosis. Neither secretion nor translocation was affected by enzymatically inactivating the cysteine protease domain of the toxin. These data demonstrate that the amino-terminal and carboxyl-terminal repeat-containing regions of the MARTX(Vv) toxin are necessary and sufficient for the delivery of effector domains and epithelial cell lysis in vitro but that effector domains are required for other cytopathic functions. Furthermore, Ca(2+)-dependent secretion of the modified MARTX(Vv) toxin suggests that nonclassical RTX-like repeats found in the carboxyl-terminal repeat-containing region are functionally similar to classical RTX repeats found in other RTX proteins.